If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -1x = 4z Reorder the terms: -1x + 3z = 4z Solving -1x + 3z = 4z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3z' to each side of the equation. -1x + 3z + -3z = 4z + -3z Combine like terms: 3z + -3z = 0 -1x + 0 = 4z + -3z -1x = 4z + -3z Combine like terms: 4z + -3z = 1z -1x = 1z Divide each side by '-1'. x = -1z Simplifying x = -1z
| 2x^2+y^2+2yz+2z^2=0 | | 157=220-u | | ×/9=1/9 | | 2x=-0.5 | | 5+2x-x+x=10+x | | 5x+17=-23 | | Y-13=-8 | | r/5.8=11.6 | | 4-4x+3=5x-2 | | -3x^2-6x+2=0 | | 253=122-y | | 0.4(x)+0.25(132-x)=38.28 | | 1/2p-15=3/4p-3 | | x-5,2,3=2,1,3 | | 8x+4=16x+8 | | 12.1=2.2m | | -y+243=290 | | 5b+3b=16 | | 12x-137=6x-11 | | (2-x)*(-3+x)=0 | | Y=4cos(4x)+3 | | 5(x-2)-(-x+3)=7 | | -1-4c=3 | | 8a+7a+3a= | | 2(n-9)-(2-n)= | | m/16=3.2 | | (0.9)2-0.3= | | 5(2-x)-(-x+3)=7 | | 8(n+9)+2(n-3)= | | 3(1-2y)=3-(7y+9) | | 6u+64=14u | | 3u-2=4(4-u)-4 |